STUDENT UNDERSTANDING OF GEOGRAPHY STKIP PGRI WEST SUMATERA (A Case Study in Regional Geography Course On Case Ambalat Island ) - RISMAN, HIDAYATUL; Rianto, M.Pd, Slamet; Putri, S.Pd, M.Si, Rozana Eka (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ This study aimed to obtain information, analyze student comprehension of geography STKIP PGRI West Sumatera (case study of regional geography course on the island Ambalat case) views of : 1) conversion, 2) interpret and 3) estimates. This study is a qualitative study, conducted on the campus of West Sumatera STKIP PGRI. Informants of this study were taken by purposive sampling technique is the determination of informants in a manner chosen with consideration and a specific purpose. Informants of this study were students of Geography Education STKIP PGRI West Sumatera who have followed the course of regional geography. The number of informants in this study were 30 students of Geography Education Program. Testing the validity of the data in the study used data analysis techniques, the validity of the data and triagulasi Results showed: 1) Understanding students of Geography Education STKIP PGRI about Case Western Sumatera Island seen from the conversion Ambalat case there are still students who have not fully understood the conversion case Ambalat Island into a symbol. 2) Understanding of Geography Education Program students STKIP PGRI about Case Western Sumatera Island seen from deciphering Ambalat Ambalat Island case there are still students who do not yet know the commencement of the case Ambalat and 3) Understanding students of Geography Education STKIP PGRI about Case Western Sumatera Island Ambalat seen from estimates of student cases have not been able to estimate the international recognition of the case Ambalat IslandÂ